Spirituality in Mary Oliver’s Poetry - Al-Zubidi, Haitham Kamil; Radhi, Noor Hassan (Al-Adab Journal, 2021)
Mary Oliver is an American poet who has been so much fascinated by the natural world since her childhood. Natural world occupies a very large space in her poetry, if not her entire poetic work. She was born in Ohio 1935, and she spent her childhood there surrounded by Nature. She graduated from high school and went to Vassar college and Ohio State University, yet she could not get a degree. She moved to New York where she met the sister of Edna St. Vincent Millay, the famous American poet and playwright. She got a closer look to Edna’s works by organizing her papers for almost seven years. As for career, she held the position at Bennington College by being the Catherine Osgood Foster Chair for Distinguished Teaching. Later on she settled in Provincetown, Massachusetts for almost forty years inspired by the natural scenes there which are conveyed in her collections.